ANALISIS KINERJA KARYAWAN DARI PERSPEKTIF KUALITAS KERJA DI BMT SAKA MADANI YOGYAKARTA - Abdul Rozaq (Universitas Sarjanawiyata Tamansiswa, 2020)
AbstractThe research was conducted to test variable influence, compensation , work discipline and workplace on performance them through the quality of work at bmt saka civil society bantul. yogyakartaThis study using the independent variable, compensation , work discipline and workplace, the dependent variable, employee performance and the variable quality of work. Intervening. Sampling technique used is. censusNamely research technique census was taken of all subjects. or populationSample were using the procedure 32 koesioner. data collectionThe analysis used the technique analysis 18.0. spss a walker And smartpls 3.2.8. The hypothesis testing in research, it can be concluded that compensation discipline, work workplace have had a positive impact on the quality of work and employee performance.But compensation not significantly to the quality and performance karyawanan.To discipline and workplace significant work on the quality of work and insignificant on performance.For quality have had a positive impact and significant work on performance.Â Keywords: Compensation , work discipline , work environment the quality of employment and employee performance